Agency modulates interactions with automation technologies. Issue 9 (2nd September 2018) - Le Goff, Kevin; Rey, Arnaud; Haggard, Patrick; Oullier, Olivier; Berberian, Bruno
Abstract: The increasing presence of automation between operators and automated systems tends to disrupt operators from action outcomes, leading them to leave the control loop. The theoretical framework of agency suggests that priming the operator about the system's upcoming behaviour could help restore an appropriate sense of control and increase user acceptance of what the system is doing. In a series of two experiments, we test whether providing information about what the system is about to do next leads to an increase in the level of user acceptance, concomitant with an increase in control and performance. Using an aircraft supervision task, we demonstrated the benefit of prime messages regarding system acceptance and performance. Taken together, our results indicate that the principles proposed by this framework could be used to improve human–machine interaction and maintain a high level of sense of control in supervisory tasks. Practitioner Summary: The out-of-the-loop performance problem is a major potential consequence of automation, leaving operators helpless to takeover automation in case of failure. Using an aircraft supervision task, the following article illustrates how the psychological approach of agency can help improving human–system interactions by designing more acceptable and more controllable automated interfaces